Brand Image on Customers Decisions to Choose Mudharabah IB Fajar Savings at PT. BPRS Fajar Sejahtera Bali - R. Agrosamdhyo (International Journal of Economics, Commerce, and Management, 2024)
The formulation of the problem in this research is: Does the quality of bank service influence the customer's decision to choose IB Fajar Mudharabah Savings at PT. BPRS Fajar Sejahtera Bali? This type of research is quantitative research and data collection methods by distributing questionnaires and documentation. The research subjects used a population of 2,764 customers and a sample of 30 customers. The analysis in this research uses IBM SPSS 25. The results of this research show there is an influence between service quality on the customer's decision to choose where t count > t table is 3.549 > 1.695. There is an influence of service quality on customers' decisions to choose IB Fajar Mudharabah Savings at PT. BPRS Fajar Sejahtera Bali.